Modeling of DSTATCOM Devices to Improve Dynamic Voltage Stability in a Microgrid with High Penetration of Motor Loads - Paredes Tapia, Luis Angel (2020)
This paper proposes and validates models of FACTS technology devices of the Synchronous Static Compensator for Distribution (DSTATCOM) type. In the first instance, a simplified DSTATCOM modeling performed through a controlled current source is presented. Subsequently, a DSTATCOM modeled through control strategies is exposed considering a PWM (Pulse-Width Modulation) converter. The proposed models of DSTATCOM devices are validated in a CIGRÉ Electrical Microgrid (MG) test system. The presence of induction motor type loads in the MG requires a considerable demand for reactive power, this causes inconveniences to maintain the Dynamic Voltage Stability (DVE). This situation is aggravated by the occurrence of failures that trigger an isolated operation of the MG. To solve these problems, a DSTATCOM device will be used. The optimal connection and location of DSTATCOM in the MG is done through an exhaustive search algorithm, considering the premise of the best performance in terms of DVE made through dynamic simulations in PowerFactory DIgSILENT. Comparatively, the results obtained for the two models performed are presented, showing the improvement of the DVE in the isolated operation of the MG with both models. Depending on the detail and scope of the studies in the MG system, you can choose between the developed DSTATCOM models. All details of models, control diagrams and data of DSTATCOM devices are provided in this document.